PETROLOGY OF MANTLE XENOLITHS FROM MEGADO AND DILO; KENYA RIFT; SOUTHERN ETHIOPIA - Orlando, Andrea; Abebe, Tsegaye; Manetti, Piero; Santo, Alba Patrizia; Corti, Giacomo (Ofioliti, 2024)
A study has been made of ultramafic xenoliths embedded in the Quaternary basanitic lavas of Dilo and Megado areas; southern Ethiopia. This is the first time that xenoliths have been found at Dilo. In both areas; the xenoliths are spinel lherzolites and pyroxenites; garnet- and/or spinel-bearing pyroxenites occasionally containing amphibole. Temperature/pressure estimates indicate that the lherzolites and most of the pyroxenites last equilibrated in the upper mantle in similar P-T conditions (T 950-1050°C at P 1.3-1.7 GPa); whereas some spinel pyroxenites equilibrated at higher temperatures ( 1150-1250°C). Based on mineral assemblage; four groups of pyroxenites were distinguished; two of which exhibit spectacular garnet coronas around spinels. Whole-rock and mineral composition (major and trace elements) indicates that garnet-free pyroxenites segregated from OIB-type melt. Successively; melt evolution caused garnet crystallisation (so that garnet bearing pyroxenites formed) and; eventually; pargasitic amphibole caused the generation of garnet- and amphibole- bearing pyroxenites with the consequent LILE-enrichment of residual melts. Melt evolution resembles that hypothesised by Bedini et al. (1997) to explain metasomatism of lherzolites based on reactive porous flow simulations. Thus; pyroxenites may represent the “counter-part” of the melts responsible of the metasomatism in this area. Furthermore; the OIB nature of parental permeating melts suggests that metasomatism (and pyroxenite genesis) was related to Quaternary magmatic activity responsible for the xenoliths ascent to the surface.